Correlation Between Family Support and Emotional Regulation with The Resilience of Breast Cancer Patients in The City of Surabaya: A Literature Review - Mauna Qurrotul Ain; Mira Triharini; Tiyas Kusumaningrum (Universitas Airlangga, 2020)
Introduction: Breast cancer incidence has increased recently. Breast cancer patients usually feel inconvenience, psychological impact, and unstable emotions. The purpose of this study is to review the literature on the relationship between family support and emotional regulation with the resilience of breast cancer patients.Methods: The review literature search uses a database